Comparative analysis of the value for money factors of PPPs between the UAE and the UK. Issue 4 (3rd April 2021) - Almarri, Khalid
Abstract: Public private partnerships (PPP) procurement instruments have been very popular tools for developing projects around the world. This is largely due to their success in bringing quality, efficiency, innovation, funds, experience and most importantly risk sharing to the projects they are involved in. This study aims to pinpoint the value for money (VFM) factors that are needed to implement PPP mechanisms in transitional economies, where the United Arab Emirates (UAE) is taken as a case study, whose findings will be contrasted to that of a UK sample, a developed economy. Relevant data was collected through a questionnaire to establish the VFM factors for each of the two countries. In this study, data was collected from 30 participants in the UAE, and 62 participants residing in the UK. A comparative analysis between the results of both countries revealed a great deal of similarity of the significant impact of the VFM factors on the assessment of PPP. The same four factors were chosen as the most important ones by both samples out of the sixteen factors for delivering VFM outcomes. These factors were optimized risk allocation, competitive bid process, improved services to the community, and clear output specification. This study contributed to practice by highlighting to the sponsors the most important VFM factors and group of factors to consider when assessing the VFM of any potential PPP project. This study also contributed to research in the field of PPPs in the UAE and the UK. The comparative analysis between the two countries highlighted the similarities and differences in the practice and opened areas for future consideration.